Calculation and Experimental Verification of the Residual Stress of Tooth Surface in Spur Gear Form Grinding - Sheng Yu; Jun Wen; Jinyuan Tang (Jixie chuandong)
The residual stress state of grinding gear has great influence on its performance, the accurate prediction and calculation of residual stress of tooth surface after grinding is the important content of gear anti - fatigue manufacture. Based on the motion analysis of form grinding and the thermo-mechanical coupling finite element simulation calculation method, the calculation method of residual stress of the tooth surface after grinding is proposed. Subsequently, the forming grinding experiment is carried out, and the residual stress of the tooth surface after grinding is measured. The measured values of the residual stress and the finite element calculation value are compared, and the correlation law between the grinding parameters and the residual stress is analyzed. The research indicates that the calculation result of the proposed form grinding model is in good agreement with the experimental results. And in the form grinding, a larger feed depth results in a smaller residual tensile stress on the tooth surface after grinding.